Réponses

2013-02-24T11:23:53+01:00

A(x) = (3x + 1)² - 5(3x+1)(x-4)

= 9x² + 6x + 1 - 15x² + 60x - 5x + 20

= -6x² + 61x + 21

 

A(x) = (3x + 1)² - 5(3x+1)(x-4)

= (3x+1)(3x+1-5x+20)

= (3x+1)(21-2x)

 

(3x+1)(21-2x) = 0

 

(3x+1)  = 0 ou (21-2x) = 0

donc 2 solutions :

x = -1/3

ou

x = 21/2

 

En espérant t'avoir aidé.

 

 

2013-02-24T11:26:15+01:00

A(x) = 9x² + 6x + 1-15x² + 55x + 20 = -6x² + 61x + 21

A(x) = (3x+1)(3x+1-5x+20) = (3x+1)(-2x + 21)

(3x+1)(-2x + 21) = 0 => x = -1/3 ou x = 10,5